Glial Cells Missing 1 Regulates Equine Chorionic Gonadotrophin Beta Subunit via Binding to the Proximal Promoter - Read, Jordan E.; Cabrera-Sharp, Victoria; Kitscha, Phoebe; Cartwright, Judith E.; King, Peter J.; Fowkes, Robert C.; de Mestre, Amanda M. (Frontiers in Endocrinology, 2018)
Equine Chorionic Gonadotrophin (eCG) is a placental glycoprotein critical for early equine pregnancy and used therapeutically in a number of species to support reproductive activity. The factors in trophoblast that transcriptionally regulate eCGβ-subunit (LHB), the gene which confers the hormones specificity for the receptor, are not known. The aim of this study was to determine if Glial Cells Missing (GCM) 1 regulates LHB promoter activity. Here, studies of the LHB proximal promoter identified four binding sites for GCM1 and Western blot analysis confirmed GCM1 was expressed in equine chorionic girdle and surrounding tissues. Luciferase assays demonstrated endogenous activity of the LHB promoter in BeWo choriocarcinoma cells with greatest activity by a proximal 335 bp promoter fragment. Transactivation studies in COS7 cells using an equine GCM1 expression vector showed GCM1 could transactivate the proximal 335 bp LHB promoter. Chromatin immunoprecipitation using primary chorionic girdle trophoblast cells showed GCM1 to preferentially bind to the most proximal GCM1 binding site over site 2. Mutation of site 1 but not site 2 resulted in a loss of endogenous promoter activity in BeWo cells and failure of GCM1 to transactivate the promoter in COS-7 cells. Together, this data shows that GCM1 binds to site 1 in the LHB promoter but also requires the upstream segment of the LHB promoter between -119 bp and -335 bp of the translation start codon for activity. GCM1 binding partners, ETV1, ETV7, HOXA13 and PITX1, were found to be differentially expressed in the chorionic girdle between days 27 and 34 and are excellent candidates for this role. In conclusion, GCM1 was demonstrated to drive the LHB promoter, through direct binding to a predicted GCM1 binding site, with requirement for another factor(s) to bind the proximal promoter to exert this function. Based on these findings, we hypothesize that ETV7 and HOXA13 act in concert with GCM1 to initiate LHB transcription between days 30 and 31, with ETV1 partnering with GCM1 to maintain transcription.